Criminal compliance: A mechanism to help prevent corruption in State procurement - Gerónimo De La Cruz, Jaime (2023)
This research arises from the need to reduce corruption within public institutions, specifically, in government procurement. At present, it is clear that corruption has reached every sector of the government, even in the most complex government systems, such as public procurement, where a large amount of money is spent to achieve a collective goal. However, such a social goal is cut short by corruption acts within public agencies when executing contracts. In this regard, to stop such illegal acts in State procurement, it is necessary to supervise the actions of procurement agents. Criminal compliance thus emerges as a solution to curb this social problem in the form of a regulatory compliance program designed to reduce the risk of corruption acts.